Enhancing Work Readiness Through Technopreneurship and Digital Literacy: A Study of Information Technology Students - Yogi Irdes Putra; Ali Idrus; Firman; Sofyan (Jurnal Penelitian Pendidikan IPA, 2026)
Digital technology has transformed labor market demands, requiring university graduates to possess comprehensive work readiness. This study analyzes the influence of technopreneurship and digital literacy on Information Technology students’ work readiness at private universities. Using a quantitative approach, 307 respondents were selected through proportional random sampling. Data were collected via Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. Findings revealed both variables significantly and positively influence work readiness, with digital literacy as the dominant factor. The R² value of 0.63 indicates that 63% of work readiness variance is explained by these factors. Results highlight the importance of integrating technopreneurship and digital literacy into higher education curricula to prepare graduates for digital industry demands. Universities should strengthen project-based learning, startup incubation programs, and applied digital training. This study provides empirical evidence of technopreneurship and digital literacy’s simultaneous effect on work readiness in developing technological ecosystems, contributing to quality education and decent work opportunities aligned with sustainable development goals.